The Prevalence of Canine Dipylidiasis in Baghdad city, Iraq‎ ‎ - Salih, Dunya AA Mohammad; Abbas , Athmar K (The Iraqi Journal of Veterinary Medicine, 2022)
Dipylidiasis is a zoonotic intestinal cestode disease caused by Dipylidium caninum. ‎The objective of this study was to investigate the prevalence of Dipylidium caninum infections ‎in dogs from Baghdad city. The study involved the impact of sexes, age, during nine months ‎‎(from January to October 2021) on dipylidiasis infection in pet and stray dogs. 108 faecal ‎samples were collected from (54 pets and 54 stray dogs) then examined for the detection of D. ‎caninum egg capsules and eggs using coprological diagnosis (flotation and sedimentation ‎methods) in the laboratory of parasitology / College of Veterinary Medicine, University of ‎Baghdad. The overall infection rate was 14.81% (16/108). The study revealed the infection rate ‎of D. caninum from pets and stray dogs was 9.26% (5/54), and 20.37% (11/54), respectively. ‎Infection rates in stray dogs were high during March, April, and May (12.5% for each month), ‎compared with pet dogs (0%, 6.25%, 6.25%) respectively, while in January, the rate of ‎infection was 0% in both types, significantly (P<0.05) during March. A significant difference ‎was recorded (P<0.01) between the sexes in both dog types, females recorded a higher 25% ‎‎(3/12) infection rate than males 19.05% (8/42) in stray dogs, compared to the females, 5.9% ‎‎(1/17) and males, 10.8% (4/37) in pet dogs, respectively. According to the age, a high infection ‎rate was found in stray dog adults (20.51%), while the infection rate was zero (0%) in pet dog ‎puppies, with a significant difference (p < 0.01) between the age groups in both types. The ‎results revealed that stray and pet dogs may play a larger role in the spread of zoonotic ‎dipylidiasis and that public health needs more concerted efforts to educate dog owners and ‎implement control programs to prevent the infective stage maturation by cutting life cycle of ‎intermediate hosts.